Control of Aerosols after Sodium Fire Accident in Integrated Fast Reactor - CUI Chunsheng, CHEN Ran, WANG Chuangao, PANG Hongchao, LUO Zhiping, HUANG Xin (Yuanzineng kexue jishu)
Styrene-acrylate emulsion fixation agent is used in control of radioactive aerosols of integrated fast reactors. In integrated fast reactor design, radioactive aerosol control represents a critical safety requirement. To mitigate hazards from sodium aerosols and other radioactive particles generated during potential sodium fire accidents in sodium processing compartments, while facilitating post-accident residue management, effective suppression of aerosol resuspension and dispersion becomes imperative. This study developed a film-forming aerosol fixing agent through emulsion polymerization using styrene (St) and butyl acrylate (BA) as primary monomers, with acrylic acid and methacrylic acid as functional monomers, specifically for sodium aerosol capture. Conditional experiments first established optimal dosages of initiator and emulsifier at 1.25wt% and 1.5wt% of total monomer mass and emulsion mass, respectively. Three fixing agent samples with varying monomer ratios (St∶BA = 1∶1, 1.75∶1, and 2∶1) were subsequently synthesized and aerosol natural settling experiments and aerosol capture experiments were designed to characterize the aerosol capture performance of the three fixative samples. An experimental setup was constructed, consisting of an aerosol capture test bench, an aerosol generator, an aerosol particle size spectrometer, and a fixed agent atomization device. The above experiment was conducted based on experimental design and experimental setup. Comparative aerosol capture experiments revealed the St∶BA=1.75∶1 formulation demonstrated superior performance, achieving 99.43% capture efficiency within 6 hours, significantly exceeding the 78.32% natural sedimentation rate observed in control trials. Resuspension tests further confirmed the agent’s effectiveness, showing aerosol resuspension rates reduced from 16.15% in natural sedimentation scenarios to merely 0.19% following aerosol fixation treatment. Microstructural analysis through SEM revealed the optimized formulation formed continuous polymer films that effectively encapsulated aerosol particles, while FTIR characterization verified successful copolymerization of functional groups enhancing interfacial interactions. The results show that the styrene-acrylate emulsion fixing agent enables superior radioactive aerosol control in sodium fire scenarios compared to passive sedimentation, with capture efficiency improvements exceeding 20 percentage points. The film-forming mechanism provides durable suppression of aerosol resuspension, reducing post-deposition particle remobilization by two orders of magnitude. The 1.75∶1 St/BA ratio optimizes the balance between polymer film flexibility and adhesion strength required for effective particle encapsulation. This research demonstrates the technical feasibility of applying polymeric fixation agents for enhanced radioactive aerosol management in advanced reactor systems, offering significant safety improvements over conventional passive containment strategies.